Tanfīdh Namūdhaja Taʿallumi Aṣ-Ṣūrati wa Aṣ-Ṣūrati li-Tarqiyati an-Našāṭi wa Natā’iji Taʿallumi aṭ-Ṭullābi fī Māddati al-Fiqhi al-Faṣli ath-Thānī bi-Maʿhadi al-Islāmī al-Khayri Funūrūku li-t-Tarbiyati al-Islāmiyyati al-Ḥadīthati al-ʿĀm ad-Dirāsī 2022–2023: Implementation of the Picture and Picture Learning Model to Improve Student Activity and Learning Outcomes in the Second-Grade Fiqh Subject at Al-Islāmi al-Khayr Funoruko Modern Islamic Educational Institute, Academic Year 2022–2023 - Rizkullah, Muhamad Fakhriyendi (Critical Review of English-Arabic World Journal, 2024)
هدف هذه البحث إلى معرفة زيادة النتيجة ونشاط الطلاب في الصف الثاني في عملية التدريس لمادة الفقه بمعهد الإسلام الخير فونوروكو للتربية الإسلامية الحديثة العام الدراسي 2022-2023 باستخدام نموذج التعلم الصورة والصورة. من نتيجة الملاحظة في المعهد الإسلام الخير فونوروكو بمادة الفقه الفصل الثاني هناك بعض المسألة التي توجد فيها يعني مهارات المعلم في التدريس ليست مبتكرة للغاية ويجعل إلى تحمل الطلاب حتى لا يهتموا بالدروس التي يقدم العلم إليهم. بذالك يسبب إلي نتائج الطلاب في الفصل و يجعل 75% من الطلاب منخفضون بنتائج تعلمهم لعلاج المشاكل القائمة ثم يقترب الباحث بالبحث الإجرائي الفصل باستخدام نموذج تعلم الصورة والصورة لترقية النشاط ونتائج تعلم الطلاب في مادة الفقه الفصل الثاني بمعهد الإسلام الخير فونوروكو للتربية الإسلامية الحديثة الهدف لهذا البحث، (1) ترقية نشاط الطلّاب للفصل الثاني في مادّة الفقه بتنفيذ نموذج تعلم الصورة والصورة (2) ترقية نتائج تعلّم الطلّاب للفصل الثاني في مادّة الفقه بتنفيذ نموذج تعلم الصورة والصورة. نتائج هذا البحث هي كما يلي (1) إن تنفيد نموذج تعلم الصورة والصورة  صالح لترقية النشاط التعلّم الطلاب في مادة الفقه لصف الثاني بمعهد الإسلام الخير فونوروكو بدليل أن الطلاب ينشطون في حل المشكلات ويشاركون في استنتاج التعلم. وبلغ نشاط الطلّاب في الدور الأوّل 75٪ مع وجود بعض التقييمات أي العاكسة في الدور الأوّل. في الدور الثاني تحسّن نشاط الطلّاب إلى 88٪ (2) إن تنفيد نموذج تعلم الصورة والصورة صالح لترقية نتائج التعلّم الطلاب في مادة الفقه لصف الثاني بمعهد الإسلام الخير فونوروكو بدليل تتحسن النتيجة في كل الدور. بعدد الطلاب الناجحون في الدور الأول هو 9 طالبا بمعدل 61،88(56%) و في الدور الثانى بعدد الطلاب الناجحون هو 13 طالبا بمعدل 70،06(81%)  .بناء على المناقشة السابقة، اقترح الباحث فيما يلي  إن تنفيد نموذج تعلم الصورة والصورة صالح لترقية النشاط و نتائج التعلّم الطلاب في مادة الفقه لصف الثاني بمعهد الإسلام الخير فونوروكو للتربية الإسلامية الحديثة   The aim of this research is to determine the improvement in student achievement and student activity in the second-grade class during the teaching of Fiqh at Al-Islam Al-Khoir Islamic Modern Educational Institute in Fonoruko for the academic year 2022–2023 through the use of the Picture and Picture learning model. Based on observations at Al-Islam Al-Khoir Fonoruko in the Fiqh subject for the second grade, several issues were found, including the lack of innovation in the teacher’s teaching methods, which caused students to become passive and uninterested in the lessons delivered. Consequently, this led to low learning outcomes, with 75% of students scoring poorly. To address these problems, the researcher applied classroom action research (CAR) using the Picture and Picture learning model to improve student activity and learning outcomes in the second-grade Fiqh subject at Al-Islam Al-Khoir Fonoruko Islamic Modern Educational Institute. The objectives of this study are: (1) to improve student activity in the second-grade Fiqh class through the implementation of the Picture and Picture learning model, and (2) to improve student learning outcomes in the second-grade Fiqh class through the same model. The results of this study are as follows: (1) The implementation of the Picture and Picture learning model is effective in improving student learning activity in the Fiqh subject for second-grade students at Al-Islam Al-Khoir Fonoruko. This is evidenced by students becoming more active in problem-solving and participating in drawing learning conclusions. Student activity in the first cycle reached 75%, although there were several aspects that required revision. In the second cycle, student activity improved to 88%. (2) The implementation of the Picture and Picture learning model is also effective in improving student learning outcomes in the Fiqh subject for second-grade students, as shown by the improvement in results in each cycle. In the first cycle, 9 students passed with an average score of 61.88 (56%), while in the second cycle, 13 students passed with an average score of 70.06 (81%). Based on the discussion above, the researcher concludes that the Picture and Picture learning model is effective in improving both student activity and learning outcomes in the second-grade Fiqh class at Al-Islam Al-Khoir Fonoruko Islamic Modern Educational Institute.